Features of patient rehabilitation after arthroscopic reconstruction of the cruciate ligaments of the knee joint - Yakovin, R. S.; Golovakha, M. L. (My University, 2025)
Cruciate ligament injuries of the knee joint are among the most common injuries among athletes, physically active individuals, and patients who have experienced significant mechanical impacts (falls, blows, accidents, etc.).
Keywords: тези доповідей